Metal Concentrations in the Water and Bedrock of Ogun River, Nigeria - Anslem Diayi; Michael Gbadebo (Applied Environmental Research, 2013)
Parts of the Ogun River basin namely Mokoloki, Brewery, Akomoje, Akin Olugbade, Lafenwa, Oyan, Arakanga, and Kara were surveyed to determine the effects of bedrock metals on the water quality of the river. Physicochemical analyses were done on the bedrock and water samples obtained while bedrock trace metal analyses were determined using the Inductively Coupled Plasma Optical Emission Spectrometry. Water trace metal analyses were carried out by Atomic Absorption Spectrometry (AAS). Data obtained were subjected to the Duncan Multiple Range Test (DMRT). Results obtained showed that Cadmium (Cd) (0.425-1.990 ppm for bedrock samples and 0.005-0.011 mg L-1 for water samples) exceeded internationally acceptable limits. Also, Lead (Pb) value for water samples (0.005-0.217 mg L-1 was reported to be higher than the internationally acceptable limits. Other values obtained for bedrock, and water samples (trace metal analysis), were lower than the internationally acceptable limits.